Metacognitive-discursive activities in Indonesian mathematics classrooms: A two-stage comparative case study - Ate, Dekriati; Kusumah, Yaya Sukjaya; Cohors-Fresenborg, Elmar (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2025)
Classroom discussions are essential for developing students’ mathematical understanding. While prior studies have examined teacher-led instruction, there remains a gap in understanding how metacognitive and discursive activities shape the quality of mathematical discussions at the whole-class level. To address this gap, this study proposes a systematic framework for analyzing public classroom discussions with a focus on metacognitive-discursive activities that support mathematical argumentation. The analysis centers on two dimensions: (1) monitoring the logical validity, correctness, and completeness of mathematical arguments, and (2) identifying how discourse quality is enhanced or obstructed by participants’ communicative strategies. This qualitative study employed a two-stage procedure: first, a fine-grained micro-level coding of classroom interactions to identify metacognitive and discursive activities, including monitoring (of terminology, methods, and argument consistency), reflection (on representational structures and methodological effectiveness), and discursive actions that either promote or hinder mutual understanding and second, a macro-level evaluation of discussion quality using a standardized rating framework. This methodological approach, applied for the first time in the Indonesian mathematics education context, enabled a more comprehensive analysis of discourse processes in whole-class discussions and helped identify phases in which strategies for enhancing the classroom discussion culture could be developed. The findings indicate that productive mathematical discussions require an environment that encourages students to articulate and critique solution strategies, justify their reasoning, and collaboratively resolve discrepancies with minimal teacher scaffolding. The study contributes to mathematics education research by providing a rigorous analytical model for examining mathematical discourse and offering evidence-based recommendations for cultivating a classroom culture that promotes deeper mathematical understanding.